Sinergi Budaya Samin Dengan Fiqih Lingkungan di Jawa Tengah - Subakir, Ahmad; Wakhidah, Nur; Muzainah, Gusti; Sadiani; Abdullah, Raihanah (Syariah: Jurnal Hukum dan Pemikiran, 2024)
This article explores the synergy between Samin culture and the concept of environmental fiqh in Central Java. This research employs qualitative methods, including in-depth observations, participatory observations, and documentation studies. This research seeks to provide a deeper insight into how local culture that has interacted with environmental fiqh can stop the plan to establish a cement factory as a pretext for national development. More specifically, this study uses the concepts of culture, ecology, and environmental fiqh to analyze the resistance of the Samin community to the plan to build the cement factory. The research findings show that the synergy of Samin culture with environmental fiqh was able to stop the plan to establish a cement factory on Mount Kendeng, Pati Regency, Central Java. This study offers a new perspective on formulating policies that are more inclusive and sustainable by strengthening the synergy between local culture and environmental fiqh principles.